2005
DOI: 10.1016/j.jtcvs.2005.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The roles of chronic pressure and volume overload states in induction of arrhythmias: An animal model of physiologic sequelae after repair of tetralogy of Fallot

Abstract: Chronic right ventricular volume overload resulted in an increased incidence of inducible ventricular and atrial arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 30 publications
(47 reference statements)
3
31
0
Order By: Relevance
“…These indices may reflect chronic right ventricular volume overload, which has been associated with an increased incidence of right-sided atrial arrhythmias. 19 The high rate of inappropriate ICD shocks consistently reported in patients with congenital heart disease likely reflects the relatively young age of the study population, the propensity for coexisting supraventricular tachyarrhythmias, and the higher susceptibility for lead failure. 20 Indeed, 21% of patients experienced late lead-related complications.…”
Section: Discussionmentioning
confidence: 94%
“…These indices may reflect chronic right ventricular volume overload, which has been associated with an increased incidence of right-sided atrial arrhythmias. 19 The high rate of inappropriate ICD shocks consistently reported in patients with congenital heart disease likely reflects the relatively young age of the study population, the propensity for coexisting supraventricular tachyarrhythmias, and the higher susceptibility for lead failure. 20 Indeed, 21% of patients experienced late lead-related complications.…”
Section: Discussionmentioning
confidence: 94%
“…There have been several animal models proposed to simulate the pathophysiological change of repaired TOF patients (7)(8)(9)(10)(11). Most of these animal models involve pulmonary valvotomy or stenting of the RVOT to create PR (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several animal models have been proposed to simulate the hemodynamic changes in repaired TOF patients by using pulmonary valvotomy or transannular patch (7)(8)(9)(10)(11). Although effective in hemodynamic simulation, the importance of electrophysiological factor was seldom addressed.…”
mentioning
confidence: 99%
“…In animal models that reproduced different physiologic states following TOF repair, those animals with chronic RV volume overload resulting from pulmonary valvotomy were significantly more likely to develop sustained atrial arrhythmias (p=0.01) [16]. Patients with atrial tachycardia have been reported to have significantly larger mean right atrial dimensions and volume compared to age-matched patients without arrhythmias [17]. Tissue Doppler imaging assessment of RV diastolic function has suggested reduced early RV diastolic velocity is significantly reduced in TOF patients that develop atrial arrhythmias [18].…”
Section: Arrhythmia Substratementioning
confidence: 99%